Pendidikan Moderasi Beragama Sebagai Landasan Pembentukan Etika Profesi Akuntan Muslim Yang Moderat - Uswatun Hasanah; Hanifah Al Hafizah; Elissa Putri Rosalia; Milana Abdillah Subarkah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to examine the role of religious moderation education in shaping the professional ethics of moderate Muslim accountants. Amid recurring cases of financial statement manipulation, collusion with clients, and unethical pressure in the accounting profession, a strong moral foundation is needed that goes beyond mere compliance with technical standards. This research uses a literature review method, analyzing books, related journals, and articles concerning religious moderation, Islamic professional ethics, and accounting ethics codes. The findings show that the four pillars of religious moderation, namely national commitment, tolerance, an anti-violence attitude, and accommodation of local cultural values, are closely aligned with the core principles of the accountant's code of ethics, namely integrity, objectivity, professional competence and due care, confidentiality, and professional behavior. Moreover, these pillars correspond with the spirit of Moderate Islam, namely tawassuth, i'tidal, tasamuh, musyawarah, ishlah, qudwah, muwathohah, and tawazun. This study concludes that strengthening religious moderation education, particularly through Al-Islam and Kemuhammadiyahan (AIK) courses in higher education, plays a strategic role in producing accountants who are principled yet not rigid, compliant with regulations yet humanist in professional practice